"A Journey into History: Eastern Europe as a Liminal Landscape in Joyce Carol Oates' Short Stories" - Bryla, Martyna Marika (My University, 2013)
This paper approaches a selection of Joyce Carol Oates’ short stories about the post-war Eastern Europe from the perspective of liminality. In the stories, Oates takes her readers for a tour of a world that no longer exists, exploring, as the title of the collection suggests, the Last Days (1984) of Eastern Europe in the grip of communism—the world divided by history and politics, where the personal has become enslaved by the political. In anthropology, the adjective “liminal” refers to the middle stage in a tripartite structure of rite of passage developed by a French ethnographer Arnold van Gennep. Those passing through a liminal phase are separated from the well-known and familiar and divested of their habitual thinking, feeling and acting. Meanwhile, they are “alternately forced or encouraged to think about their society, their cosmos, and the powers that generate and sustain them” (Turner 105). Therefore, liminality implies a deep transformation of the subject who is supposed to emerge from the rite not only equipped with fresh knowledge but also as a new being. In recent years, the concept has proved to offer a valuable tool for studying literature in terms of both form and content. In this paper, I propose to read Oates’ protagonists’ encounters with Eastern Europe as liminal in nature. I suggest that by travelling behind the Iron Curtain the Americans become immersed in a kind of rite of passage which makes them, at least for a while, forgo the world as they know it and enter a liminal phase charged both with dangers and possibilities. In consequence, the European capitals featured in the stories, Berlin, Warsaw and Budapest, become sites of personal refection, inner conflict, and even physical and mental transformation. At the same time, Oates gives her readers a taste of what life was like behind the Iron Curtain, juxtaposing the Eastern and the Western in a poignant, if at times stereotypical manner. In more general terms, this paper hopes to demonstrate that liminality provides a valid framework to study the way Eastern Europe functioned in the American imaginary, more as a mental concept rather than a specific physical region.
Keywords: Oates, Joyce Carol - Crítica e interpretación; Eastern Europe; Liminality; Literature